Day/night change in orientation of the orb weaver Azilia guatemalensis (Araneae: Tetragnathidae) - Barrantes Montero, Gilbert (2021)
Most orb weavers orient downward on their orbs, but here we describe an unusual pattern of orientation in the tetragnathid Azilia guatemalensis. This species changes its orientation on the hub with a consistent day/night pattern. During the day, the spiders orient upward on the orb, but orient downward during the night. In addition, we found that the spiders construct a few silk lines that connect the hub with a sparse mesh near the upper edge of the orb which, in turn, is connected to the substrate. When disturbed, the spider runs using these lines and hides on the substrate, suggesting that its upward orientation during the day, and its escape behaviour, may be a response to diurnal enemies.